Divorce and Its Practices Before A Religious Court; A Perspective Analysis of Islamic Legal - Qowiyul Iman, Rifqi; Joni, Joni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research discusses divorce in Islam, known as